Abruption of the common carotid artery origin with no neurological impairment : Abrupcija na polazištu zajedničke karotidne arterije bez neurološkog deficita - Figl, Josip (Array, 2021)
Objective: In this case, we present a patient who despite iatrogenic common carotid artery disruption had no neurological impairment after vascular reconstruction. Case report: During the neck dissection in a young patient a complete abruption of the common carotid artery occurred. Median sternotomy was done for proximal bleeding control. Vascular reconstruction was done using temporary carotid shunting. The patient had no neurological consequences afterward. Conclusion: The lesion of major neck vessels is one of the most severe complications during the surgery which must be dealt with as soon as possible in best way in order to avoid permanent brain damage. In situations of iatrogenic lesions of major neck arteries heparin admission, which is usually normal therapy during vascular reconstruction, is not an option due to abrupt and uncontrollable bleeding. Thus, establishing surgically proximal and distal vascular control over the bleeding artery by vessel clamping and urgent placing of temporary intraluminal carotid shunting and best medical intraoperative therapy in this critical period of surgery might be the crucial therapeutic moment for brain protection.